Florid osseous dysplasia, lesi radiopak bilateral pada radiograf panoramik - Ratih Trikusumadewi Lubis; Fitri Angraini Nasution; Azhari Azhari; Farina Pramanik (Ikatan Radiologi Kedokteran Gigi Indonesia, 2019)
Objectives: The aim of this report is to present a case of florid osseous dysplasia and understand its characteristics from panoramic radiography. Case Report: A 47-years-old female patient came to the oral and maxillofacial radiology department at Dental and Oral Hospital of Universitas Padjadjaran to take panoramic radiography. Patient’s chief complaints were pain on tooth 46 after being extracted about 4 days ago with numbness on the extraction area. Panoramic radiograph showed radioopaque lesions in the extraction area surrounded by a thin radiolucent area. In the periapical region of tooth 36 and 47 showed the same radiopaque image as tooth 46. The radiodiagnostic suspect of the lesions was bilateral florid osseous dysplasia in the posterior region of the mandible. Conclusion: The images of florid osseous dysplasia from panoramic radiography are radioopaque, well-defined, sclerotic border, and having soft tissue capsule when the lesion is immature condition. The most common condition of FOD affect both upper and lower jaw, but if the lesion only occur in one jaw, the lesion commonly happen in mandible with exact location is more posterior than canine teeth.